High temperature resistant polyolefin automotive interior hot melt adhesive and preparation method thereof
By introducing functional polymers and other additives into polyolefin hot melt adhesives, multiple network structures are constructed, and the shortcomings of existing hot melt adhesives in high temperature resistance, low temperature flexibility, adhesiveness and other aspects in automotive interior applications are solved, and high-performance, environmentally friendly and multi-functional hot melt adhesives are achieved.
Patent Information
- Application Number
- CN202410717005.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-06-04
AI Technical Summary
The existing polyolefin hot melt adhesives have problems such as poor high temperature resistance, insufficient low temperature flexibility, poor adhesiveness to polar substrates, short opening time, poor aging resistance and large VOC release in automotive interior applications, which cannot meet the strict requirements of the new generation of automotive interior parts.
Styrene-based thermoplastic elastomers and random polypropylene are used as main resins, and by introducing functional polymers, reactive rubbers, block copolymers, tackifying resins and other additives, a composite toughening and tackifying system with multiple network structures is constructed to achieve dynamic coupling between chemical reactions and physical effects, forming a multiphase structure with both hardness and softness and gradient interpenetration.
It significantly improves the high temperature resistance, low temperature flexibility, bonding strength, aging resistance and process performance of hot melt adhesives, and at the same time reduces the VOC content, achieving high-performance, environmentally friendly and multi-functional hot melt adhesives.
Smart Images

Figure BDA0004875863560000141 
Figure BDA0004875863560000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hot melt adhesives, in particular to a high temperature resistant polyolefin automobile interior hot melt adhesive and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of the automobile industry and the increasing requirements of consumers for the quality of the in-car environment, the bonding technology of automotive interior parts is facing unprecedented challenges. Traditional solvent-based and water-based adhesives can no longer meet the increasingly stringent environmental protection and energy-saving requirements due to VOC emissions and energy consumption issues. Hot melt adhesives have been widely used in the field of automotive interior bonding due to their advantages such as 100% solid content, no solvent, low energy consumption, and easy construction, and have become the current mainstream bonding material.
[0003] Among the many types of hot melt adhesives, polyolefin hot melt adhesives occupy an important position in the bonding of automotive interiors due to their excellent mechanical properties, electrical insulation, water resistance and environmental protection. However, as automotive interior parts develop towards lightweight, integrated and multi-material directions, higher requirements are placed on the performance of hot melt adhesives, which are mainly reflected in the following aspects:
[0004] 1. Poor high temperature resistance, unable to meet long-term use requirements. The temperature of automotive interior parts can reach as high as 80-90°C under the sun in summer. The softening point of ordinary polyolefin hot melt adhesive is low (usually <100°C), and it is easy to soften and deform at high temperatures, resulting in bonding failure. Improving the heat resistance of hot melt adhesive and ensuring its bonding reliability in high temperature environments is an urgent problem to be solved.
[0005] 2. Insufficient low-temperature flexibility, prone to brittle fracture. Under low-temperature conditions in winter, ordinary polyolefin hot melt adhesives for automotive interior parts will become hard and brittle, and their impact resistance will decrease. Under vibration and impact, interfacial debonding or structural damage is likely to occur. Therefore, improving the low-temperature flexibility of hot melt adhesives and improving their impact resistance are crucial to ensuring the durability of interior parts bonding.
[0006] 3. Poor adhesion to polar substrates, prone to interfacial debonding. With the widespread use of polar materials such as engineering plastics, metals, and glass in automotive interiors, conventional non-polar polyolefin hot melt adhesives have poor bonding compatibility with them, and are prone to interfacial debonding under high temperatures or long-term loads. How to improve the adhesion of hot melt adhesives to polar substrates without deteriorating material compatibility is a technical challenge.
[0007] 4. Short open time, not suitable for complex processes. The shapes of automotive interior parts tend to be more complex, which puts higher requirements on the construction process of hot melt adhesive. The open time of conventional hot melt adhesive is usually <30s, and the operable time window after glue application is small, which cannot meet the assembly requirements of large interior parts. Extending the open time of hot melt adhesive and improving its process adaptability are of great significance to improving the manufacturing efficiency of interior parts.
[0008] 5. Poor aging resistance and unstable performance in long-term use. The service life of automotive interior parts is usually >10 years, which puts stringent requirements on the aging resistance of hot melt adhesives. Conventional hot melt adhesives are prone to thermal oxidation degradation and photooxidation degradation under long-term high temperature or ultraviolet radiation, resulting in decreased mechanical properties and reduced bonding strength. Improving the anti-aging performance of hot melt adhesives and ensuring their performance stability in long-term use is a difficult problem that needs to be solved urgently.
[0009] 6. The amount of VOC released is large, which makes it difficult to meet environmental protection requirements. During the processing and use of hot melt adhesives, volatile organic compounds such as small molecular monomers and additives remaining in the raw materials will continue to be released, polluting the interior environment of the car. With the increasingly stringent environmental regulations, low VOC or even zero VOC has become the development trend of hot melt adhesives. How to minimize the VOC content while ensuring the performance of hot melt adhesives is a severe test facing hot melt adhesive manufacturers.
[0010] In summary, the existing polyolefin hot melt adhesive still has many deficiencies in terms of high temperature resistance, low temperature flexibility, bonding reliability, process adaptability, aging resistance, environmental protection, etc., which are far from meeting the stringent requirements of the bonding of the new generation of automotive interior parts. It is urgent to develop a new generation of high-performance, multifunctional, and environmentally friendly polyolefin hot melt adhesive. This is not only an inevitable requirement for the development of automotive interior bonding technology, but also the only way for the transformation and upgrading of the adhesive industry and green development. Summary of the invention
[0011] It is under this background that the present invention proposes a high temperature resistant polyolefin automotive interior hot melt adhesive and a preparation method thereof, aiming at the common technical problems existing in the application of existing polyolefin hot melt adhesives in automotive interiors. The hot melt adhesive uses styrene thermoplastic elastomers and random polypropylene as the main resins, and by introducing key additives such as functionalized polymers, reactive rubbers, block copolymers, and tackifying resins, a composite toughening and tackifying system with a multiple network structure is constructed, which realizes the dynamic coupling of chemical reactions and physical actions at the molecular scale, and forms a multiphase structure with both rigidity and flexibility and gradient interpenetration in microscopic morphology, and finally achieves a leap-forward improvement in the mechanical properties, bonding properties, thermal properties, aging resistance, and process performance of the hot melt adhesive. The hot melt adhesive has excellent high temperature resistance, low temperature flexibility, high peel strength, long open time, excellent aging resistance, and low VOC characteristics, representing a major breakthrough in polyolefin hot melt adhesive technology, and points out the direction for the development of a new generation of green, environmentally friendly, high-performance, and multifunctional hot melt adhesives. The high temperature resistant polyolefin automotive interior hot melt adhesive developed by the present invention can be widely used not only for bonding various interior parts such as ceilings, carpets, seats, door panels, dashboards, but also for other automotive supporting fields such as exterior parts, sound insulation cotton, and sealing strips. It is of great significance to improve the bonding performance of automotive parts, improve automobile manufacturing efficiency, and promote the green development of the automotive industry. At the same time, the new concept of molecular design and new ideas for formula optimization advocated by the hot melt adhesive have important reference value for enriching and developing hot melt adhesive bonding theory and technology, and will surely promote technological progress and industrial upgrading in the adhesive industry.
[0012] The invention discloses a high temperature resistant polyolefin automotive interior hot melt adhesive, comprising the following components in parts by weight: 35-45 parts of propylene-ethylene random copolymer polypropylene, 8-15 parts of syndiotactic polypropylene, 3-8 parts of maleic anhydride grafted polypropylene, 3-8 parts of hydroxyl terminated liquid polybutadiene, 8-15 parts of styrene-α-methylstyrene block copolymer, 20-35 parts of hydrogenated C5 petroleum resin, 3-8 parts of oligomeric α-olefin, and 0.2-1.0 parts of antioxidant and 0.2-1.0 parts of light stabilizer.
[0013] Specifically, the propylene-ethylene random copolymer polypropylene has a number average molecular weight of 150,000-250,000, a weight average molecular weight of 900,000-1.5 million, a molecular weight distribution of 5-8, an amorphous region content of 55-65%, and a density of 0.86-0.90 g / cm 3 , the melt flow rate is 2-10g / 10min.
[0014] Specifically, the number average molecular weight of the syndiotactic polypropylene is 100,000-200,000, and the density is 0.90-0.92 g / cm 3 , melting point is 155-165℃, crystallinity is 75-85%, and tensile yield strength is >500MPa.
[0015] Specifically, the maleic anhydride grafting rate of the maleic anhydride grafted polypropylene is 0.5-2.0wt%, the melt flow rate of the polypropylene homopolymer matrix is 50-200g / 10min, and the number average molecular weight of the polypropylene homopolymer matrix is 50,000-100,000.
[0016] Specifically, the hydroxyl-terminated liquid polybutadiene has a number average molecular weight of 2000-5000, a functionality of 1.8-2.2, a hydroxyl value of 40-60 mgKOH / g, a glass transition temperature Tg of -70--50°C, and a trans-1,4 structure content of >85%.
[0017] Specifically, the number average molecular weight of the styrene-α-methylstyrene block copolymer is 100,000-200,000, the styrene content is 60-80wt%, the α-methylstyrene content is 20-40wt%, and the glass transition temperature Tg>120°C.
[0018] Specifically, the softening point of the hydrogenated C5 petroleum resin is 125-135°C and the density is 0.98-1.02 g / cm 3 , acid value <1mg KOH / g, iodine value <10gI2 / 100g, color <3.
[0019] Specifically, the low-poly α-olefin has a dynamic viscosity of 5-500 cSt at 100° C., a flash point of >200° C., a pour point of <-40° C., a molecular weight distribution Mw / Mn of <1.5, and an amorphous content of 100%.
[0020] Specifically, the antioxidant is B225; the light stabilizer is selected from any one of UV 1577, UV 1164, UV 1600, and UV400.
[0021] A method for preparing a high temperature resistant polyolefin automotive interior hot melt adhesive comprises the following steps:
[0022] (1) Heat the reactor to 180-200°C and continue stirring;
[0023] (2) adding maleic anhydride grafted polypropylene into a reaction kettle, stirring and melting for 20-40 minutes, then adding propylene-ethylene random copolymer polypropylene, and continuing to stir for 30-60 minutes until it is completely melted and uniform;
[0024] (3) adding syndiotactic polypropylene and continuing stirring for 20-40 minutes, and then sequentially adding hydroxyl-terminated liquid polybutadiene, oligomeric α-olefin, antioxidant and light stabilizer, stirring for 10-20 minutes after each component is added;
[0025] (4) Cool the reactor to 160-180°C, add styrene-α-methylstyrene block copolymer and hydrogenated C5 petroleum resin, and continue stirring for 30-60 minutes until the mixture becomes uniform and transparent;
[0026] (5) Raise the temperature of the reactor to 180-200°C and keep it warm for 30-60 minutes;
[0027] (6) Evacuate at 180-200°C for 20-40 min;
[0028] (7) The vacuum is stopped, and the melt is extruded through the extruder head and then cooled to obtain a hot melt adhesive product.
[0029] Compared with the prior art, the high temperature resistant polyolefin automotive interior hot melt adhesive and the preparation method thereof of the present invention can achieve the following beneficial effects:
[0030] 1. The present invention utilizes the high-temperature esterification reaction between maleic anhydride grafted polypropylene and hydroxyl-terminated liquid polybutadiene to form dynamic covalent bonding. At the same time, maleic anhydride grafted polypropylene can also be partially grafted with propylene-ethylene random copolymer polypropylene to form a large number of entanglements. The two synergistically construct a strong and powerful dual network structure. When heated, the elastic chemical crosslinking and flexible physical entanglement can be quickly broken and reorganized, dissipating stress concentration and preventing crack propagation, thereby greatly improving the high-temperature strength and toughness of the material, which is manifested as high bonding strength and small creep deformation; when the temperature is lowered, the crosslinked network can be frozen and solidified, locking the reinforcement effect and ensuring bonding reliability. It is worth mentioning that covalent crosslinking has a certain reversibility, which is conducive to the secondary melt processing of hot melt adhesives.
[0031] 2. The styrene-α-methylstyrene block copolymer and syndiotactic polypropylene used in the present invention have typical "rigid and flexible" structural characteristics. The styrene segment and syndiotactic polypropylene molecular chain in the styrene-α-methylstyrene block copolymer both contain a large number of rigid benzene rings or regular sequences. During the melt blending process, the two are selectively compatible due to the "co-solvent effect", which can effectively induce syndiotactic polypropylene to form highly oriented structures such as lamellar crystals or needle crystals, thereby improving the crystallinity and crystallization perfection. At the same time, the α-methylstyrene flexible chain segment of the styrene-α-methylstyrene block copolymer will be dispersed in the amorphous region of the propylene-ethylene random copolymer polypropylene, which has a certain toughening effect on the amorphous region. The synergistic capacity expansion of the rigid and flexible segments can moderately improve the rigidity of the system, without loss of flexibility, and simultaneously improve the heat deformation temperature and mechanical strength.
[0032] 3. A major problem of polyolefin hot melt adhesives is that the introduction of polar groups will deteriorate compatibility, resulting in a contradiction between mechanical properties and process properties. The present invention cleverly utilizes the MAH group grafted with maleic anhydride grafted polypropylene and the methyl groups in the molecular chains of propylene-ethylene random copolymer polypropylene and syndiotactic polypropylene to achieve "polarity matching", which not only ensures the compatible dispersion of maleic anhydride grafted polypropylene and the matrix, but also maintains good interfacial adhesion. In addition, similar polar group distribution also exists in the molecular chain of styrene-α-methylstyrene block copolymer, which can further improve the compatibility between styrene-α-methylstyrene block copolymer and maleic anhydride grafted polypropylene, propylene-ethylene random copolymer polypropylene, and syndiotactic polypropylene. The introduction of reactive groups maintains a dynamic balance with the non-polarity of the main resin, which is an ingenious design of the present invention.
[0033] 4. The present invention selectively selects hindered phenol antioxidants and UV absorbers, which have good compatibility with the matrix, are not easy to migrate and precipitate, and can form uniformly dispersed "isolation points" inside the system to capture free radicals and interrupt the degradation chain reaction; the low-molecular-weight low-poly α-olefins have moderate molecular weights, excellent thermal stability and surface enrichment properties, and can migrate to the surface of the matrix during high-temperature melting to form a low-surface-energy "isolation layer" to inhibit the invasion of external oxygen and heat. The polymer antioxidant and the low-molecular-weight α-olefin lubricant form a defense-in-depth system inside and outside the system, effectively blocking thermal oxidation degradation, avoiding the loss of small-molecule plasticizers, and realizing the controlled slow release of hot melt adhesive aging.
[0034] 5. Another highlight of the present invention is the use of hydrogenated C5 petroleum resin with a high softening point (>120°C) as a tackifier. Its molecular weight is moderate. On the one hand, it can maintain melt viscosity at high temperatures and strengthen mechanics; on the other hand, it can selectively dissolve in the amorphous region of propylene-ethylene random copolymer polypropylene, increase system flexibility, and improve adhesion. Due to the use of highly hydrogenated modification, the thermal stability and weather resistance of C5 petroleum resin are greatly improved. It is worth mentioning that the dispersion of C5 petroleum resin in the system is closely related to the crystallization induction of syndiotactic polypropylene, the compatibilization of styrene-α-methylstyrene block copolymer, and the graft crosslinking of maleic anhydride grafted polypropylene. The impact on the performance of the system is complex, and the dosage needs to be accurately adjusted to achieve overall efficiency.
[0035] 6. Throughout the formulation design of the present invention, it involves multi-level chemical and physical processes such as polymerization reaction, grafting reaction, condensation reaction, crystallization, phase separation, and surface migration. These processes occur dynamically and influence each other throughout the entire life cycle of hot melt adhesive processing and use, and jointly shape the microscopic and macroscopic properties of hot melt adhesive. For example, the esterification crosslinking of maleic anhydride grafted polypropylene and hydroxyl-terminated liquid polybutadiene, and the physical entanglement of maleic anhydride grafted polypropylene and propylene-ethylene random copolymer polypropylene / syndiotactic polypropylene molecular chains exist simultaneously and compete in the dynamic temperature field; the co-crystallization behavior of styrene-α-methylstyrene block copolymer and syndiotactic polypropylene is subject to the comprehensive constraints of factors such as the grafting rate of maleic anhydride grafted polypropylene, the softening point of C5 petroleum resin, and the molecular weight of oligomeric α-olefins; in the high-temperature molding process, how the above reactions, crystallizations, and phase separations are balanced determines the processing performance and mechanical properties of the system. It can be said that the performance regulation of the system of the present invention is a process of "dynamic game", in which multiple components compete and cooperate at different levels and dimensions, and ultimately achieve dynamic optimization of structure and performance, which is difficult to achieve with conventional hot melt adhesives.
[0036] In summary, the core innovation of the high-temperature resistant polyolefin automotive interior hot melt adhesive of the present invention lies in the use of cutting-edge theories of polymer chemistry and physics to accurately design and regulate the components, structure, and performance of the hot melt adhesive system in a multi-level, multi-dimensional, and dynamic coordinated manner, achieving the organic coupling of chemical reactions and physical effects at the molecular level, constructing an interpenetrating structure of cross-linked networks and block expansion in microscopic morphology, and achieving the best balance of strength, toughness, heat resistance, aging resistance, adhesion, and process in macroscopic performance. This hot melt adhesive molecular design concept based on "structure-performance integration" not only solves the technical bottleneck of polyolefin hot melt adhesive applications in high-end fields, but also provides new ideas and methods for the innovation and upgrading of hot melt adhesives and even the entire adhesive field, and has important academic value and engineering guidance significance. The present invention takes the multi-level synergistic efficiency enhancement of polymers as the core, overcomes the multiple contradictions of materials, processes and performance, and realizes the "three highs and one low" (high strength, high toughness, high heat resistance and low VOC) with excellent physical strength, reliability in use and environmental friendliness. It represents a major breakthrough in polyolefin hot melt adhesive technology and will surely lead the transformation and upgrading of the adhesive industry towards green, high-end and intelligent manufacturing. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] High temperature resistant polyolefin automotive interior hot melt adhesive, comprising the following components (parts by mass):
[0040] Propylene-ethylene random copolymer polypropylene 35 parts (Mw = 900,000, PDI = 5, amorphous region content 55%, density 0.86g / cm 3 , MFR = 2g / 10min);
[0041] 8 parts of syndiotactic polypropylene (mmmm = 98%, Mn = 100,000, density 0.90g / cm 3 , Tm = 155 ° C, crystallinity 75%, tensile yield strength 500 MPa);
[0042] Maleic anhydride grafted polypropylene 3 parts (MAH grafting rate 0.5%, matrix MFR = 50g / 10min, matrix Mn = 50,000);
[0043] 3 parts of hydroxyl-terminated liquid polybutadiene (Mn=2000, functionality 1.8, hydroxyl value 40 mgKOH / g, Tg=-70°C, trans-1,4 structure content 85%);
[0044] 8 parts of styrene-α-methylstyrene block copolymer (Mn=100,000, PS content 60%, Tg=120°C);
[0045] 20 parts of hydrogenated C5 petroleum resin (softening point 125℃, density 0.98g / cm 3 , acid value <1mgKOH / g, iodine value <10gI2 / 100g, color <3);
[0046] Oligomeric α-olefin 3 parts (viscosity @ 100°C = 5 cSt, flash point 200°C, pour point -40°C, Mw / Mn = 1.5, amorphous content 100%);
[0047] Composite antioxidant B2250.2 parts and UV 15770.2 parts.
[0048] The preparation method of high temperature resistant polyolefin automotive interior hot melt adhesive comprises the following steps:
[0049] (1) The reactor temperature was raised to 180°C and the rotation speed was 50 rpm;
[0050] (2) Maleic anhydride grafted polypropylene was added and stirred to melt for 20 minutes, and propylene-ethylene random copolymer polypropylene was added and stirred for 30 minutes;
[0051] (3) Add syndiotactic polypropylene and stir for 20 minutes, then add hydroxyl-terminated liquid polybutadiene, oligomeric α-olefin, antioxidant and light stabilizer in sequence, and stir for 10 minutes each;
[0052] (4) Cooling to 160°C, adding styrene-α-methylstyrene block copolymer and hydrogenated C5 petroleum resin, and stirring for 30 min;
[0053] (5) Heat to 180°C and keep warm for 30 min;
[0054] (6) 180°C vacuum - 0.08 MPa 20 min;
[0055] (7) Stop vacuuming, melt extrusion molding, and cooling.
[0056] Example 2
[0057] High temperature resistant polyolefin automotive interior hot melt adhesive, comprising the following components (parts by mass):
[0058] Propylene-ethylene random copolymer polypropylene 40 parts (Mw = 1.2 million, PDI = 6.5, amorphous region content 60%, density 0.88g / cm 3 , MFR = 5g / 10min);
[0059] 12 parts of syndiotactic polypropylene (mmmm = 99%, Mn = 150,000, density 0.91 g / cm3, Tm = 160°C, crystallinity 80%, tensile yield strength 600 MPa);
[0060] Maleic anhydride grafted polypropylene 5 parts (MAH grafting rate 1%, matrix MFR = 100g / 10min, matrix Mn = 75,000);
[0061] 5 parts of hydroxyl-terminated liquid polybutadiene (Mn=3500, functionality 2.0, hydroxyl value 50 mgKOH / g, Tg=-60°C, trans-1,4 structure content 90%);
[0062] Styrene-α-methylstyrene block copolymer 12 parts (Mn = 150,000, PS content 70%, Tg = 130°C);
[0063] 25 parts of hydrogenated C5 petroleum resin (softening point 130℃, density 1.00g / cm 3 , acid value 0.5mgKOH / g, iodine value 5g I2 / 100g, color 2);
[0064] Oligomeric α-olefin Oligomeric α-olefin 5 parts (viscosity @ 100°C = 50 cSt, flash point 250°C, pour point -50°C, Mw / Mn = 1.3, amorphous content 100%);
[0065] Composite antioxidant B2250.5 parts (molecular weight 3000) and UV 4000.5 parts.
[0066] The preparation method of high temperature resistant polyolefin automotive interior hot melt adhesive comprises the following steps:
[0067] (1) The reactor temperature was raised to 190°C and the rotation speed was 75 rpm;
[0068] (2) Maleic anhydride grafted polypropylene was added and stirred to melt for 30 minutes, and propylene-ethylene random copolymer polypropylene was added and stirred for 45 minutes;
[0069] (3) Add syndiotactic polypropylene and stir for 30 minutes, then add hydroxyl-terminated liquid polybutadiene, oligomeric α-olefin, antioxidant and light stabilizer in sequence, stirring each for 15 minutes;
[0070] (4) Cooling to 170°C, adding styrene-α-methylstyrene block copolymer and hydrogenated C5 petroleum resin, and stirring for 45 minutes;
[0071] (5) Heat to 190°C and keep warm for 45 min;
[0072] (6) 190℃ vacuum -0.06MPa 30min;
[0073] (7) Stop vacuuming, melt extrusion molding, and cooling.
[0074] Example 3
[0075] High temperature resistant polyolefin automotive interior hot melt adhesive, comprising the following components (parts by mass):
[0076] Propylene-ethylene random copolymer polypropylene 45 parts (Mw = 1.5 million, PDI = 8, amorphous region content 65%, density 0.90 g / cm3, MFR = 10 g / 10 min);
[0077] 15 parts of syndiotactic polypropylene (mmmm = 99.5%, Mn = 200,000, density 0.92g / cm3, Tm = 165℃, crystallinity 85%, tensile yield strength 700MPa);
[0078] Maleic anhydride grafted polypropylene 8 parts (MAH grafting rate 2%, matrix MFR = 200g / 10min, matrix Mn = 100,000);
[0079] 8 parts of hydroxyl-terminated liquid polybutadiene (Mn=5000, functionality 2.2, hydroxyl value 60 mgKOH / g, Tg=-50°C, trans-1,4 structure content 95%);
[0080] 15 parts of styrene-α-methylstyrene block copolymer (Mn=200,000, PS content 80%, Tg=140°C);
[0081] 35 parts of hydrogenated C5 petroleum resin (softening point 135℃, density 1.02g / cm 3 , acid value 0.1mgKOH / g, iodine value 1gI2 / 100g, color 1);
[0082] Oligomeric α-olefin 8 parts (viscosity @ 100°C = 500 cSt, flash point 300°C, pour point -60°C, Mw / Mn = 1.1, amorphous content 100%);
[0083] Composite antioxidant B2251 parts and UV 11641 parts (molecular weight 3000).
[0084] The preparation method of high temperature resistant polyolefin automotive interior hot melt adhesive comprises the following steps:
[0085] (1) The reactor was heated to 200°C and rotated at 100 rpm;
[0086] (2) Maleic anhydride grafted polypropylene was added and stirred to melt for 40 minutes, and propylene-ethylene random copolymer polypropylene was added and stirred for 60 minutes;
[0087] (3) Add syndiotactic polypropylene and stir for 40 minutes, then add hydroxyl-terminated liquid polybutadiene, oligomeric α-olefin, antioxidant and light stabilizer in sequence, and stir for 20 minutes each;
[0088] (4) Cooling to 180°C, adding styrene-α-methylstyrene block copolymer and hydrogenated C5 petroleum resin, and stirring for 60 min;
[0089] (5) Heat to 200°C and keep warm for 60 min;
[0090] (6) 200℃ vacuum - 0.05MPa 40min;
[0091] (7) Stop vacuuming, melt extrusion molding, and cooling.
[0092] Example 4
[0093] High temperature resistant polyolefin automotive interior hot melt adhesive, comprising the following components (parts by mass):
[0094] Propylene-ethylene random copolymer polypropylene 42 parts (Mw = 1.35 million, PDI = 7, amorphous region content 62%, density 0.89g / cm 3 , MFR = 7g / 10min);
[0095] 10 parts of syndiotactic polypropylene (mmmm = 98.5%, Mn = 180,000, density 0.915 g / cm3, Tm = 162°C, crystallinity 82%, tensile yield strength 650 MPa);
[0096] Maleic anhydride grafted polypropylene 6 parts (MAH grafting rate 1.5%, matrix MFR = 150g / 10min, matrix Mn = 80,000);
[0097] 6 parts of hydroxyl-terminated liquid polybutadiene (Mn=4000, functionality 2.1, hydroxyl value 55 mgKOH / g, Tg=-55°C, trans-1,4 structure content 92%);
[0098] 10 parts of styrene-α-methylstyrene block copolymer (Mn=180,000, PS content 75%, Tg=135°C);
[0099] 30 parts of hydrogenated C5 petroleum resin (softening point 132°C, density 1.01g / cm3, acid value 0.3mgKOH / g, iodine value 3gI2 / 100g, color 1.5);
[0100] Oligomeric α-olefin 6 parts (viscosity @ 100°C = 200 cSt, flash point 280°C, pour point -55°C, Mw / Mn = 1.2, amorphous content 100%);
[0101] Composite antioxidant B225 0.8 parts and UV 1600 0.8 parts.
[0102] The preparation method of high temperature resistant polyolefin automotive interior hot melt adhesive comprises the following steps:
[0103] (1) The reactor temperature was raised to 195°C and the rotation speed was 90 rpm;
[0104] (2) Maleic anhydride grafted polypropylene was added and stirred to melt for 35 minutes, and propylene-ethylene random copolymer polypropylene was added and stirred for 50 minutes;
[0105] (3) Add syndiotactic polypropylene and stir for 35 minutes, then add hydroxyl-terminated liquid polybutadiene, oligomeric α-olefin, antioxidant and light stabilizer in sequence, stirring for 18 minutes each;
[0106] (4) Cooling to 175°C, adding styrene-α-methylstyrene block copolymer and hydrogenated C5 petroleum resin, and stirring for 55 min;
[0107] (5) Heat to 195°C and keep warm for 50 min;
[0108] (6) 195°C vacuum - 0.055 MPa for 35 min;
[0109] (7) Stop vacuuming, melt extrusion molding, and cooling.
[0110] Comparative Example 1 (corresponding to Example 1, lacking maleic anhydride grafted polypropylene)
[0111] Components: 35 parts of propylene-ethylene random copolymer polypropylene, 8 parts of syndiotactic polypropylene, 3 parts of hydroxyl-terminated liquid polybutadiene, 8 parts of styrene-α-methylstyrene block copolymer, 20 parts of hydrogenated C5 petroleum resin, 3 parts of oligomeric α-olefin, 0.2 parts of antioxidant, and 0.2 parts of light stabilizer.
[0112] Preparation method: Same as Example 1, except that maleic anhydride grafted polypropylene is not added in step (2), and the other conditions remain unchanged.
[0113] Comparative Example 2 (corresponding to Example 2, hydroxyl-terminated liquid polybutadiene was replaced by liquid polybutadiene)
[0114] Components: propylene-ethylene random copolymer polypropylene 40 parts, syndiotactic polypropylene 12 parts, maleic anhydride grafted polypropylene 5 parts, liquid polybutadiene 5 parts (Mn=3500, functionality 2.0), styrene-α-methylstyrene block copolymer 12 parts, hydrogenated C5 petroleum resin 25 parts, oligomeric α-olefin oligomeric α-olefin 5 parts, antioxidant 0.5 parts, light stabilizer 0.5 parts.
[0115] Preparation method: Same as Example 2, except that the hydroxyl-terminated liquid polybutadiene in step (3) is replaced by liquid polybutadiene, and the other conditions remain unchanged.
[0116] Comparative Example 3 (corresponding to Example 3, styrene-α-methylstyrene block copolymer is replaced by SBS)
[0117] Components: propylene-ethylene random copolymer polypropylene 45 parts, syndiotactic polypropylene 15 parts, maleic anhydride grafted polypropylene 8 parts, hydroxyl-terminated liquid polybutadiene 8 parts, SBS 15 parts (Mn=150,000, styrene content 30%), hydrogenated C5 petroleum resin 35 parts, oligomeric α-olefins 8 parts, antioxidant 1 part, light stabilizer 1 part.
[0118] Preparation method: Same as Example 3, except that in step (4), the styrene-α-methylstyrene block copolymer is replaced by SBS, and the other conditions remain unchanged.
[0119] Comparative Example 4 (corresponding to Example 4, C5 petroleum resin was replaced by C9 petroleum resin)
[0120] Components: 42 parts of propylene-ethylene random copolymer polypropylene, 10 parts of syndiotactic polypropylene, 6 parts of maleic anhydride grafted polypropylene, 6 parts of hydroxyl-terminated liquid polybutadiene, 10 parts of styrene-α-methylstyrene block copolymer, 30 parts of hydrogenated C9 petroleum resin (softening point 130°C, density 1.01g / cm3, color>6), 6 parts of oligomeric α-olefins, 0.8 parts of antioxidants, and 0.8 parts of light stabilizers.
[0121] Preparation method: Same as Example 4, except that in step (4), C5 petroleum resin is replaced by C9 petroleum resin, and the other conditions remain unchanged.
[0122] Comparative Example 5 (corresponding to Example 1, oligomeric α-olefin is replaced by paraffin)
[0123] Components: 35 parts of propylene-ethylene random copolymer polypropylene, 8 parts of syndiotactic polypropylene, 3 parts of maleic anhydride grafted polypropylene, 3 parts of hydroxyl-terminated liquid polybutadiene, 8 parts of styrene-α-methylstyrene block copolymer, 20 parts of hydrogenated C5 petroleum resin, 3 parts of paraffin (melting point 60°C), 0.2 parts of antioxidant, and 0.2 parts of light stabilizer.
[0124] Preparation method: Same as Example 1, except that the oligomeric α-olefin in step (3) is replaced by paraffin, and the other conditions remain unchanged.
[0125] Comparative Example 6 (corresponding to Example 2, without adding antioxidant and light stabilizer)
[0126] Components: propylene-ethylene random copolymer polypropylene 40 parts, syndiotactic polypropylene 12 parts, maleic anhydride grafted polypropylene 5 parts, hydroxyl terminated liquid polybutadiene 5 parts, styrene-α-methylstyrene block copolymer 12 parts, hydrogenated C5 petroleum resin 25 parts, oligomeric α-olefin oligomeric α-olefin 5 parts.
[0127] Preparation method: Same as Example 2, but without adding antioxidant and light stabilizer, and other conditions remain unchanged.
[0128] Comparative Example 1 lacks maleic anhydride grafted polypropylene, which will affect the compatibility and interfacial adhesion between PP and hydroxyl-terminated liquid polybutadiene, and the high-temperature mechanical properties will decrease;
[0129] Comparative Example 2 uses liquid polybutadiene to replace hydroxyl-terminated liquid polybutadiene. The liquid polybutadiene molecular chain does not contain reactive hydroxyl groups, and dynamic covalent crosslinking cannot be formed, resulting in reduced heat resistance and creep resistance.
[0130] Comparative Example 3 uses ordinary SBS to replace styrene-α-methylstyrene block copolymer. SBS has a low styrene content and a low glass transition temperature, and has a poor compatibilization effect on syndiotactic polypropylene and limited improvement in heat resistance.
[0131] Comparative Example 4 uses C9 petroleum resin with a low degree of hydrogenation, which has many residual double bonds, poor thermal stability and weather resistance, and dark color, which affects the appearance of the final product;
[0132] Comparative Example 5 uses low melting point paraffin to replace oligomeric α-olefins. Although it can also play a role in reducing viscosity and increasing plasticity, it is easy to migrate and precipitate at high temperatures, resulting in a sticky surface of the adhesive layer and an increase in VOC content.
[0133] In Comparative Example 6, no antioxidant and light stabilizer are added. Under the action of high temperature and UV, the polymer matrix is easily degraded, the thermal stability and weather resistance are greatly reduced, and the service life is limited.
[0134] Test Method:
[0135] 1. Open time test (refer to ASTM D4497-2018)
[0136] (1) Place the hot melt adhesive sample in a melting kettle at 180°C and stir until it is uniformly molten;
[0137] (2) At 180°C, use a 200 μm coater to apply a uniform film on the surface of a standard paper substrate (size 100 mm × 300 mm);
[0138] (3) Start timing when coating is completed. Take a 25 mm × 100 mm paper strip every 5 seconds, stick it vertically on the coated surface, and press lightly for 2 seconds.
[0139] (4) After curing at room temperature for 24 hours, check the adhesion of each paper strip to the substrate. The longest time when the paper strip can be completely bonded without any paper scraps remaining is the open time.
[0140] 2. Room temperature bonding performance test
[0141] (1) Prepare three groups of PP board bonding specimens according to the provisions of GB / T 7124-2008, with a hot melt adhesive coating thickness of 200 μm;
[0142] (2) The specimens were cured under standard conditions (23 ± 2 °C, 50 ± 5% RH) for 24 h;
[0143] (3) Use an electronic universal testing machine to perform shear strength test at a speed of 5 mm / min, record the maximum force at break, and calculate the bonding strength.
[0144] 3. Heat resistance test
[0145] (1) Prepare three groups of PP board bonding specimens according to the provisions of GB / T 7124-2008, with a hot melt adhesive coating thickness of 200 μm;
[0146] (2) The sample is kept at 90±2℃ for 500h;
[0147] (3) Remove the sample, restore it under standard conditions for 24 hours, and then perform a shear strength test using the room temperature bonding performance test method.
[0148] 4. High temperature and high humidity performance test
[0149] (1) Prepare three groups of PP board bonding specimens according to the provisions of GB / T 7124-2008, with a hot melt adhesive coating thickness of 200 μm;
[0150] (2) The sample is kept at 90±2℃ and 95±5%RH for 500h;
[0151] (3) Remove the sample, restore it under standard conditions for 24 hours, and then perform a shear strength test using the room temperature bonding performance test method.
[0152] 5. Creep performance test (1) Prepare PP board bonding specimens according to the provisions of GB / T 7124-2008, with a hot melt adhesive coating thickness of 200 μm; (2) Place the specimens in a 90°C oven and test the creep deformation under a constant load of 0.1 MPa, and record the deformation percentage after 48 h.
[0153] 6. VOC content test (1) According to the provisions of GB / T 27630-2011, weigh 10g of hot melt adhesive sample and place it in a 20mL headspace bottle and seal it; (2) Fill the bottle with nitrogen, heat and desorb it at 180℃ for 2h, and analyze the VOC composition and content using gas chromatography-mass spectrometry (GC-MS).
[0154] 7. Test method for color change ΔE: Test method for color change ΔE:
[0155] Apply hot melt adhesive on a white PP board to prepare a 10 cm × 10 cm sample, and measure the initial color data L0, a0, and b0;
[0156] Place the sample in a 90°C oven for 500 hours, and then measure the color data L1, a1, and b1 after aging;
[0157] Calculate the color difference ΔE as follows * :
[0158]
[0159] This step details the testing process for color change (color difference) ΔE, including sample preparation, aging treatment, and calculation of the final color difference value.
[0160]
[0161] Table 1
[0162] Combining the test results in Table 1, we can find that:
[0163] (1) From the opening time, it can be seen that the embodiments of the present invention are all above 400 seconds, which can meet the requirements of longer operation time in complex processes, while the comparative examples are less than 400 seconds, which has greater limitations;
[0164] (2) Under normal temperature, heat resistance, high temperature and high humidity conditions, the bonding strength of the embodiments is significantly higher than that of the comparative examples, especially the strength of embodiment 3 is ≥8.2 MPa under the above conditions, which fully proves its excellent bonding reliability;
[0165] (3) After heat aging for 500 h, the color change of the embodiment is ΔE*≤1.2, which is better than that of the comparative example, indicating that the use of hydrogenated C5 petroleum resin can obtain better long-term heat and weather resistance; in contrast, comparative example 4 uses C9 petroleum resin with low hydrogenation degree, and the color changes significantly after aging;
[0166] (4) Comparative Example 1 did not use maleic anhydride to graft polypropylene, and Comparative Example 2 used liquid polybutadiene instead of hydroxyl-terminated liquid polybutadiene, both of which resulted in low heat-resistant bonding strength due to the lack of chemical crosslinking; the SBS in Comparative Example 3 had a low glass transition temperature and poor heat resistance improvement effect;
[0167] (5) Although the low melting point paraffin in Example 5 can play a certain lubricating role, its melting point is too low and the bonding strength retention rate is low at high temperature; Comparative Example 6 lacks an antioxidant, resulting in a significant decrease in bonding performance after aging and a large color difference.
[0168] (6) From the creep performance, it can be seen that the creep deformation of the examples is controlled within 3%, indicating that the dynamic cross-linked network structure can effectively inhibit high-temperature creep and maintain the stability of the thickness of the adhesive layer; in contrast, the creep deformation of the comparative examples is generally larger, and it is easy to produce obvious deformation under long-term stress, resulting in a decrease in the structural performance of the bonding part;
[0169] (7) From the VOC content, it can be seen that the examples are generally lower than 100 μg / g, which is much better than the comparative examples. This is due to the isolation effect formed by the high molecular weight antioxidant and the oligomeric α-olefin at the interface, which can significantly reduce the precipitation of harmful volatiles. In contrast, the comparative example 5 uses low melting point paraffin, which migrates and precipitates in large quantities at high temperatures, and the VOC content is as high as 195 μg / g. The comparative example 6 lacks an antioxidant, and a large number of degraded small molecules are generated during the high temperature aging process, and the VOC content is as high as 220 μg / g.
[0170] (8) Combining the creep performance, VOC content, color change and other data, it can be seen that the hot melt adhesive of the present invention has achieved comprehensive breakthroughs in heat resistance, aging resistance, and pollution-free. By forming a dynamic cross-linking structure and relying on the synergistic capacity expansion of block copolymers, the mechanical properties and creep resistance of the hot melt adhesive at high temperatures are significantly improved. By introducing high molecular weight antioxidants and low molecular weight α-olefins, a multi-level thermal oxidation degradation inhibition mechanism is constructed, thereby achieving dual stability of the color and VOC release of the hot melt adhesive at high temperatures.
[0171] In summary, the hot melt adhesive of the present invention achieves excellent bonding strength (>8.0MPa), heat resistance (>95%) and weather resistance (ΔE*<1.2) while taking into account a long open time (>400s). The overall performance comprehensively surpasses the comparative examples and the prior art. In particular, the molecular design strategy of using dynamic cross-linked maleic anhydride grafted polypropylene and high crystalline syndiotactic polypropylene for synergistic toughening, and high softening point hydrogenated C5 petroleum resin and high molecular weight antioxidant for synergistic anti-aging overcomes the bottleneck problem of traditional polyolefin hot melt adhesive in automotive interior applications. While improving the performance of hot melt adhesive, the present invention also takes into account environmental protection and long-term reliability, embodies the refined innovation of formula and process, and has a milestone significance for promoting the upgrading of hot melt adhesive in the field of automotive interior parts. The hot melt adhesive of the present invention takes dynamic covalent cross-linking as the core, and cleverly couples innovative mechanisms such as multi-component synergistic enhancement, surface interface regulation, and long-term anti-aging, thereby overcoming multiple technical bottlenecks in the application of polyolefin hot melt adhesive in high-end automotive interior parts. Compared with conventional hot melt adhesive formulas, the present invention has achieved all-round breakthroughs in terms of bonding strength, heat deformation resistance, color stability, VOC control, etc., and has achieved a high balance of interface strength, cohesion, thermal resistance and environmental friendliness, which is a paradigm revolution in the field of automotive interior bonding. The multiple synergistic enhancement system constructed by the present invention provides new ideas and methods for the molecular design and formula optimization of high-performance hot melt adhesives, and has important guiding significance for promoting the green transformation and upgrading of the adhesive industry.
[0172] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. High temperature resistant polyolefin automotive interior hot melt adhesive, characterized by , including the following components in parts by mass: 35-45 parts of propylene-ethylene random copolymer polypropylene, 8-15 parts of syndiotactic polypropylene, 3-8 parts of maleic anhydride grafted polypropylene, 3-8 parts of hydroxyl-terminated liquid polybutadiene, 8-15 parts of styrene-α-methylstyrene block copolymer, 20-35 parts of hydrogenated C5 petroleum resin, 3-8 parts of oligomeric α-olefin, and 0.2-1.0 parts of antioxidant and 0.2-1.0 parts of light stabilizer; The propylene-ethylene random copolymer polypropylene has a number average molecular weight of 150,000-250,000, a weight average molecular weight of 900,000-1.5 million, a molecular weight distribution of 5-8, an amorphous region content of 55-65%, and a density of 0.86-0.90 g / cm 3 , melt flow rate is 2-10g / 10min; The number average molecular weight of the syndiotactic polypropylene is 100,000-200,000, and the density is 0.90-0.92 g / cm 3 , melting point is 155-165℃, crystallinity is 75-85%, tensile yield strength>500MPa; The maleic anhydride grafted polypropylene has a maleic anhydride grafting rate of 0.5-2.0 wt %, a melt flow rate of the polypropylene homopolymer matrix of 50-200 g / 10 min, and a number average molecular weight of the polypropylene homopolymer matrix of 50,000-100,000; The hydroxyl-terminated liquid polybutadiene has a number average molecular weight of 2000-5000, a functionality of 1.8-2.2, a hydroxyl value of 40-60 mgKOH / g, a glass transition temperature Tg of -70--50°C, and a trans-1,4 structure content of>85%; The number average molecular weight of the styrene-α-methylstyrene block copolymer is 100,000-200,000, the styrene content is 60-80wt%, the α-methylstyrene content is 20-40wt%, and the glass transition temperature Tg>120°C; The softening point of the hydrogenated C5 petroleum resin is 125-135°C and the density is 0.98-1.02 g / cm 3 , acid value <1mg KOH / g, iodine value <10gI2 / 100g, color <3; The low-poly alpha-olefin has a dynamic viscosity of 5-500 cSt at 100° C., a flash point of >200° C., a pour point of <-40° C., a molecular weight distribution Mw / Mn of <1.5, and an amorphous content of 100%.
2. The high temperature resistant polyolefin automotive interior hot melt adhesive according to claim 1, characterized in that , the antioxidant is B225; the light stabilizer is selected from any one of UV 1577, UV 1164, UV 1600, and UV 400.
3. The method for preparing the high temperature resistant polyolefin automotive interior hot melt adhesive according to any one of claims 1 to 2, characterized in that , comprising the following steps: (1) heating the reactor to 180-200°C and continuously stirring; (2) adding maleic anhydride grafted polypropylene to the reactor, stirring and melting for 20-40 minutes, adding propylene-ethylene random copolymer polypropylene, and continuing to stir for 30-60 minutes until it is completely melted and uniform; (3) adding syndiotactic polypropylene and continuing to stir for 20-40 minutes, and then adding hydroxyl-terminated liquid polybutadiene, oligomeric α-olefin, antioxidant and light stabilizer in sequence, each component being added After adding, stir for 10-20 minutes; (4) cool the reactor to 160-180°C, add styrene-α-methylstyrene block copolymer and hydrogenated C5 petroleum resin, and continue stirring for 30-60 minutes until it becomes uniform and transparent; (5) heat the reactor to 180-200°C and keep it warm for 30-60 minutes; (6) vacuumize at 180-200°C for 20-40 minutes; (7) stop vacuuming, extrude the melt through the extruder head, and obtain the hot melt adhesive product after cooling.
Citation Information
Patent Citations
Adhesive composition comprising amorphous propylene / ethylene copolymers and polyolefins
CN111433271A